Hubungan Latihan Keselamatan, Peraturan dan Prosedur Keselamatan Terhadap Prestasi Keselamatan Pekerja GIATMARA Perak - Muhamad Rosly, Talib (2020)
Safety performance play an important role in the development of workplace occupational safety management, as well as ensuring safety compliance and safety participation within an organization. It also contributes to the successful implementation of the accident prevention program. In this study two independent variables (IV) were identified namely safety training, safety rules and procedures. Meanwhile, a dependent variable (DV) has been identified that is the safety performance among employees at work. The quantitative method was used in this study involving 128 respondents among the GIATMARA Perak employees. Regression analysis shows that safety training, safety rules and procedures have a significant positive relationship with safety performance. This study has suggested that organizations should give priority to improving employee safety prevention programs. Next, employee characteristics should be considered in the process of conducting safety training analysis.